ANALISIS KELAYAKAN USAHA SAYURAN HIDROPONIK DI KOTA BANJARBARU KALIMANTAN SELATAN - Mahyudi, Fitri; Husinsyah (Fakultas Pertanian UVAYA Banjarmasin, 2024)
Hydroponics comes from two Greek syllables, namely hydro which means water and ponos which means power. The definition of hydroponics is cultivating plants without using a planting medium in the form of soil which is replaced with water and other media are added such as gravel, sand or white cork. Based on the background and problem formulation that has been put forward, the aim of this research is to analyze the feasibility of the hydroponic business. Hydroponik farmer Banjarbaru based on non-financial aspects and analyzing the feasibility of the hydroponics business. Hydroponik farmer based on financial aspects. This research was conducted in Landasan Ulin District, Banjarbaru City, South Kalimantan Province. This research was chosen purposively for the reason that Banjarbaru City, especially Landasan Ulin District, has many hydroponic businesses. Research data collection was carried out from May 2024 to June 2024. After that, an analysis was carried out regarding financial aspects consisting of costs and income along with profits. Hydroponik farmer is analyzed using ROI (Return on Investment), NPV (Net Present Value), IRR (Internal Rate of Return), Net B/C ratio, PP (Payback Period), and BEP (Break Event Point). Based on the results of the analysis and discussion, this research is concluded as follows: From a non-financial aspect, Hidroponik FarmerBanjarbaru has been said to be feasible to run, provided that environmental aspects must be improved. Handling of production waste must be managed better, not just piled up at the back of the garden. From a financial aspect, Hydroponik farmer has been said to be feasible to run because it has an ROI value of 24.17%, an NPV of Rp. 79,557,052, IRR of 18.36 %, Net B/C ratio of 1.78, Payback Period of 6 years, 1 months, 16 days, BEP price of Rp. 14,557.60 per kilogram and production BEP of 4.571 per year